Characterization of Starch Granaule of Local Water Yam (Dioscorea alata L.) from Lermatang, Tanimbar Island District, Maluku: Characterization of Starch Granule of Dioscorea alata L. - Sinay, Hermalina; Karuwal, Ritha Lusian; Fauziah, Fauziah; Anaktototy , Helena (Journal of Tropical Life Science, 2024)
Most tuberous crops, for instance, the yam, whose scientific name is Dioscorea alata, have food reserves in the form of starch in tubers. Characterization of starch grains of a plant species is pertinent to uncover information on plant taxonomic traits and identify their potential use as food and industrial raw materials. The study aimed to determine the characteristics of starch grains of water yam from Lermatang village, Tanimbar Islands Regency. This study isolated and submitted six accessions of water yam in Lermatang Village. The morphological inspection of the plants used the Descriptor for Yam from IPGRI, and sample preparation for observing starch grains employed the fresh section method. The six accessions of D. alata found in Lermatang village, Tanimbar Islands, were Uwi Merah, Uwi Gula, Uwi Pingingsian, Uwi Babulu, Uwi Akiakab, and Uwi Petatas. These yam varieties show differences in their tubers' shape and colors. The study found that starch granules of D. alata in each accession varied in terms of granule shape and hilus type. The starch granules revealed dominant triangular, oval, and elliptical shapes and eccentric and concentric hilus types. The starch grain diameter in the six accessions of Uwi was categorically large (44.88 – 57.5 µm), with Uwi Petatas being the largest. Previous reports have shown that accessions having large starch granule types could be further developed into an array of foods, thus conveying the promising use of the Uwi Petatas for such a purpose.